Strategic Business Planning in a Competitive Market: A Case Study of a Building Materials Retailer in a Growing Region - Muroqi, M. Arfi; Arimbawa, Putu Adi Putra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to analyze the business conditions of Toko Bangunan Arfillah, a building materials retailer in Nganjuk Regency, and to formulate strategic recommendations to strengthen competitiveness and support business development amid increasing competition in the construction industry. Design/Methodology/Approach – This study employs a qualitative research approach. Data were collected through interviews and direct observations of the company’s operations. The analysis focuses on identifying internal and external factors affecting business competitiveness, including financial conditions, market competition, and opportunities for business expansion. Findings – The results indicate that Toko Bangunan Arfillah has a relatively stable financial condition; however, intense competition among building materials retailers in Nganjuk Regency remains a major challenge. To address this challenge, expanding market reach through digital promotional channels, particularly social media, is recommended to increase brand visibility, attract customers, and improve business competitiveness. These strategies are expected to support sustainable business growth in the developing construction market. Originality/Value This research is original in focusing on business planning for a building materials store within a developing regional market context. The findings provide practical value by offering marketing and competitive strategies tailored to small retail businesses in the construction sector.